Public Speaking Anxiety of University Students in EFL Context - Novelia Fathikasari; Agus Gozali; Devinta Puspita Ratri (STKIP Singkawang, 2022)
Public speaking anxiety poses great challenges to developing these skills. It is estimated that approximately 15% to 30% of the general population suffer from public speaking anxiety, which is the most common type of social phobia. Excessive public speaking anxiety can lead to enormous stress and frustration, impaired speech performance, and further avoidance of social situations that require making public presentations, especially for students. This study aims to investigate the level and the factors that mostly occurred among university students in public speaking. The researchers used a questionnaire of Public Speaking Anxiety (PSA) by Noorrachima (2020) and made the senior students of the English Department as the respondents for this research. The result of the study showed that the PSA level of the seniors of ELEP UB is high and the general sense factor is the highest chosen factor that triggers their public speaking anxiety.